Consumer Satisfaction Using e-Wallets - Heru Kresnha Reza; Melly Susanti (East Asian Journal of Multidisciplinary Research, 2022)
According to Ministerial Regulation No. 14 of 2017 IKM is a tool to measure the level of community satisfaction as service users and improve the quality of public services. The purpose of this study was to measure the level of community satisfaction in the village. Calculation Method Satisfaction value is "weighted average value of each service element". The results showed that 9 indicators; Requirements have a very good value, Mechanisms and system procedures are not good, Time for completion of Kuang Good, Costs / Tariffs are very good, Product Specifications, Types of Service are very good, Competence of Implementers are very good, Behavior of Implementers is very good, Handling of complaints and suggestions is very good, facilities very good.